La Dobroudja au carrefour des Europes - Bernard Lory (Cahiers Balkaniques)
Dobrudzha is a region where Romano‑Greek contacts have been very active. As a whole, it is a place of geographical and historical contacts in Europe.This paper considers different approaches in a geographical overview: Dobrudzha as part of a danubian, pontic, steppic or carpathic ensemble. At different times, when different ways of transportation are used for economic exchanges, and under different political constraints, the region played different roles.A second part considers Dobrudzha according to political power. It has been controlled for a long time by thalassocraties, during the Antique and Medieval periods. When included into empires, Dobrudzha was left as a periphery, as the Danube was constantly a northern border. It became the favorite battleground for the Russian and the Ottoman empires in the xviii‑xixth centuries. With the emergence of the national states, Dobrudzha became an apple of discontent between Romania and Bulgaria. In order to solve it the most dramatic solution ever invented by nationalism was applied: an exchange of population, which, strangely enough, did not cause any noticeable embitterment.The third part is devoted to a family of prominent provincialists, the Teodorovs. They came from Eastern Bulgaria to Tulcea after the Crimean war and seem to have undergone a quick Hellenization during twenty years. With the political turning point of 1877‑1878 their national choices change: part of the family settles in Bulgaria, when the other stays in Romania.